PENGARUH GAYA HIDUP, KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN SHOPEE PAYLATER MASYARAKAT KOTA SURABAYA - Valdi Ramadhan Jaya Saputra; Tri Sudarwanto (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This research is to find out the variables of lifestyle, trust, and ease of influence partially on purchasing decisions using Shopee Paylater for the people of Surabaya city and also want to know the variables of lifestyle, trust, and ease of influencing simultaneously or jointly influencing purchasing decisions using the community's Shopee Paylater city ​​of Surabaya. This research uses descriptive quantitative. In this study, the population used by all Shopee Paylater users in the city of Surabaya used the "non-probability sampling" sampling technique using the Lemeshow formula to determine the sample in this study of 96 residents of the city of Surabaya. The analysis used, multiple linear regression analysis. The calculation of multiple linear regression in this study uses the SPSS 25.0 for windows program. The results of the study show that lifestyle, trust, and convenience have a partial and simultaneous significant influence on purchasing decisions using Shopee Paylater. Keywords: Ease Of Use; Lifestyle; Purchase Decision; Trust; Shopee Paylater